The coca enclosure: Autonomy against accumulation in Colombia. (January 2021) - Dest, Anthony
Highlights: Forced eradication does not work: it pushes coca-growers into new areas, where they expand drug trafficking networks. The proliferation of coca cultivations in southwestern Colombia undermines black and indigenous struggles for autonomy. Drug trafficking imposes an extractive relationship upon land and life, leading local inhabitants to call it an "anti-culture." Illicit economies associated with drug trafficking deepen capitalist relations and reproduce the structural inequalities of society. Abstract: This article analyzes a relatively new phenomenon in northern Cauca: the massive expansion of coca cultivations. After decades of intense forced eradication campaigns promoted by the U.S. government, the so-called "War on Drugs" failed at achieving its stated aim. Instead, these militaristic policies pushed coca growers to find more remote places to cultivate coca in different parts of the county. In northern Cauca, coca cultivations are strongly associated with a wave of "colonization" ( colonización ) by coca growers displaced by Plan Colombia. In addition to the crops, these settlers also brought what some local inhabitants call the "anti-culture of coca, " which is associated with new forms of consumerism, violence, and an extractive relationship to the land. This ethnography explores coca's power to transform social and economic relations, and it reveals how the structural inequalities in Colombian society are reproduced in regions where it is cultivated.